EFFECT OF STRUCTURED AND REGULAR PHYSICAL ACTIVITY ON CARDIOVASCULAR CONDITIONING IN HIGH SCHOOL STUDENTS - Sara Thaqi; Hamish Kerr; Mikhail Torosoff (Elsevier, 2023)
Therapeutic Area: Other: Cardiovascular Conditioning in Adolescence Background: Cardiovascular conditioning is an important health benefit of regular physical activity in adults with and without cardiovascular disease. Effects of regular physical activity and athletic participation on cardiovascular conditioning in high school students were not well studied. Methods: A single high-school study cohort included 229 consenting students, 15.4+/-1.1 years old, 121 identified as females. A five-minute YMCA exercise step test was performed. Resting heart rate (HR), lowest heart rate during voluntary breath-holding, immediate post-exercise, and 3-minute post-exercise heart rates were recorded. For analysis, students were sequentially grouped according to the self-reported prior participation in high school athletics, current participation in high school athletics, and independent consistent physical activity at least 3 times per week. Results: Resting (81.8±14.1 vs. 90.5±15.7 bpm, p<0.001), breath holding (77.4±12.8 vs. 84.8±16.1 bpm, p=0.001), peak exercise (120.5±29.2 vs. 137.7±26.7 bpm, p<0.001), and recovery HR (89.7±17.1 vs. 104.9±16.5 bpm in the rest of the cohort, p<0.001) were significantly lower in students who were currently enrolled in high-school athletics. Significantly lower heart rates were also noted in students who reported prior athletic participation: resting (82.4±13.5 vs. 91±16.5 bpm, p<0.001), breath holding (77.9±12.9 vs. 85.4±16.4 bpm, p<0.001), peak exercise (121.4±27.6 vs. 139.2±27.8 bpm, p<0.001), and recovery HR (90±15.7 vs. 106.8±20.5 bpm in the rest of the cohort, p<0.001). Finally, any consistent participation in physical activity was also associated with significantly lower resting (83.3±14.9 vs. 90.5±15.5 bpm, p<0.001), breath holding (78.6±13.2 vs. 84.9±16.5 bpm, p=0.001), peak exercise (121.3±27.6 vs. 140.5±27.3 bpm, p<0.001), and recovery HR (92.3±18.9 vs. 104.9±19.1 bpm in the rest of the cohort, p<0.001). Conclusions: In high-school students, prior or current participation in athletic activities or being consistently physically active are associated with significantly lower resting, peak exercise, and recovery heart rates suggestive of better cardiovascular conditioning. In addition, decreased heart rate with breath holding suggest resting augmentation of vagal tone in physically active high school students. This data provides objective quantification and confirms benefit of regular exercise in high school students.